THE IMPACT OF INFORMATION TECHNOLOGY(IT) ON SUPPLYCHAIN AGILITY - PATRICA UMUTONI (UGANDA CHRISTIAN UNIVERSITY, 2024)
The dissertation aimed at finding out the impact of Information Technology (IT) on supply chain agility with a case study of Century Bottling Company (Coca-Cola). The study sought to achieve three objectives: to establish the contribution of technological infrastructure on supply chain agility in Century Bottling Company, to assess the contribution of digital solution on supply chain agility in Century Bottling Company and to examine the contribution of integration and connectivity on supply chain agility in Century Bottling Company. To achieve these objectives, a mixed methods research approach was adopted. Data was collected through a close-ended questionnaire and interviews with the different departments at Century Bottling Company. 60 returned the responses.50 of which filled the questionnaires and 10 were interviewed. The response rate was 75% in this case. Krejcie and Morgan (1970), a rate of 50% and above is acceptable, this was regarded as a representative sample for subsequent studies. This research highlights IT as a critical enabler of agility in non-traditional supply chain contexts, emphasizing its role in enhancing operational effectiveness and humanitarian outcomes. Furthermore the study underscores the critical role of digital solutions in improving operational efficiencies and overall supply chain performance. The study highlights that organizations leveraging integrated supply chain solutions can achieve higher operational efficiency and adaptability, crucial for sustaining competitive advantage